2021
DOI: 10.29333/iji.2021.14440a
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Design Thinking in Improving Student Creativity Skills and Entrepreneurial Alertness

Abstract: This research aims to examine the effectiveness of entrepreneurship learning with the Stanford D School design thinking approach and to make students more actively involved in learning activities so that their learning experiences can develop creative skills and entrepreneurial alertness. The underlying theory of the design thinking approach comes from the Experiential Learning Theory. This quasi-experiment was conducted by distributing questionnaires before and after the implementation of the learning approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The bad category of Empathize and Define stages found in this study is related to the lack of competence and creative thinking. To follow what has been suggested by Pratomo et al (2021), more effort due to the result of this study is urgently needed. By developing further implementation of the Design Thinking concept, there will be a higher sensitivity to the problems faced and push the culinary business actors to create a creative product idea based on these problems as emphasized by Tu et al (2018).…”
Section: 84% Goodmentioning
confidence: 63%
See 1 more Smart Citation
“…The bad category of Empathize and Define stages found in this study is related to the lack of competence and creative thinking. To follow what has been suggested by Pratomo et al (2021), more effort due to the result of this study is urgently needed. By developing further implementation of the Design Thinking concept, there will be a higher sensitivity to the problems faced and push the culinary business actors to create a creative product idea based on these problems as emphasized by Tu et al (2018).…”
Section: 84% Goodmentioning
confidence: 63%
“…It is found that the Design Thinking process is very appropriate to be used during the early stages of product development. Studies that measured the implementation of the Design Thinking concept have been carried out by Tu et al (2018) and Pratomo et. al (2021).…”
Section: Testmentioning
confidence: 99%
“…Therefore, entrepreneurial skills consist of three, namely (1) technical skills, (2) management skills, and (3) business and personal entrepreneurial skills (Cooney, 2012;Faris, 2018;Sousa & Almeida, 2014). Based on the categories of basic skills and entrepreneurial skills, the classification of entrepreneurial skills is as follows: (1) conceptual skills (Politis, 2005), (2) creative skills (Pratomo et al, 2021), (3) managing skills (Cooney, 2012), (4) communication and interaction skills (Faris, 2018;Sousa & Almeida, 2014), and (5) skills to develop striving techniques (Cooney, 2012).…”
Section: Entrepreneurship Skillsmentioning
confidence: 99%
“…AbduRofiq (2015) states that the current national economy is largely driven by the contribution of the creative industry by involving many young people who have creativity and innovation oriented to Micro, Small and Medium Enterprises (MSMEs). So to face the MEA, Indonesia's young generation cannot only rely on academic ability, but must be able to act creatively and innovatively to create jobs by becoming entrepreneurs (Pratomo & Wardani, 2021).…”
Section: Introductionmentioning
confidence: 99%